Pengujian Perangkat Lunak Sistem Informasi Penilaian Siswa dengan Teknik Boundary Value Analysis Menggunakan Metode Black Box Testing - Alifia Puspaningsih; Dimas Nugroho; Robby Jordan; Yoga Pratama; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In this research, the software to be tested is the student assessment application. With this application, it is expected to make it easier to present student assessments. The student's assessment will enter the database and the application can calculate the absence score, assignment score, uts score, uas score and the average score of the student. Each student only needs a grade validation to be input into the student assessment application. Student assessment data can be viewed by the supervising teacher in the form of data with name, attendance and subject information. Using methods when conducting research helps you create reports based on the data obtained during the research. Our group used the Boundary Value Method. Testing software in this way includes representative limits in the scope. The boundary analysis technique helps determine the lower limit and upper limit of the tested student data. Student assessment data including name, Nrp, daily grades, midterm grades and final exam scores were displayed along with user-entered total grade data and calculated and interpreted averages. It is concluded that testing the application by focusing on the input and output shows. From this we can conclude that the black-box testing of the application is only focused on the inputs and outputs that indicate whether the developed application conforms to a particular description.